First record of Saguinus fuscicollis melanoleucus (Miranda Ribeiro, 1912) in the Peruvian Amazon - Mena, José Luis (2007)
The fist record of Saguinus fuscicollis melanoleucus to the Peruvian Amazon is reported. This subspecies was registered by wildlife census and by an occasional record from the headwaters of the Breu and Beu rivers near to the limit with Brazil in the district of Yurua, department of Ucayali. The habitat of Saguinus fuscicollis melanoleucus in Peru includes primary forest and forests with Guadua sp. This place is inhabited by Amahuaca (Peruvian side) and Kashinawa (Brazilian side) indigenous communities.